Development of the first constitution by Bogd khan’s government - S., Otgonjargal (Acta Mongolica, 2018)
Early in the ХХ century, the Bogd Khan’s government launched the development of the Constitution, had got translated the constitutions of about 10 countries like America, England, and Japan and produced a document which contained an analytical conclusion of those international constitutions. Consequently, a draft constitution was produced under the name “State rights”. The draft was produced on the example of the Constitution of England and was directed towards creating a constitutional monarchy. In 1914, the State Upper and Lower Khürals started functioning officially following the letter of request for creation of the State Khürals was sent to the Bogd Khan and got his approval. The State Upper Khüral was composed of lords and noblemen whereas the Lower Khüral was composed of administrators and clerks of local settlements. Generally speaking, the State Upper and Lower Khürals were established on the example of the Upper and Lower Houses of the English Parliament. Thus, it could be said that the foundation of democracy was laid down in Mongolia with the creation of a universal parliamentary system of governance in the country in the early XX century.